Economically Sustainable Growth of Perovskite Photovoltaics Manufacturing - Mathews, Ian; Sofia, Sarah; Ma, Erica; Jean, Joel; Laine, Hannu S.; Siah, Sin Cheng; Buonassisi, Tonio; Peters, Ian Marius (Joule, 2020)
The significant capital expense of photovoltaics manufacturing has made it difficult for new cell and module technologies to enter the market. We present two technoeconomic models that analyze the sustainable growth of perovskite manufacturing for an R2R single-junction technology and a perovskite-silicon tandem module, focusing on the impacts of economies of scale and average selling price on profitability. We establish a cost range of 3.30/W to 0.53/W for flexible modules manufactured in factory sizes ranging from 0.3 MW/year to 1 GW/year. In addition, we model the cost to manufacture a tandem module consisting of a single-junction perovskite cell stacked in 4-terminal configuration onto a silicon cell and show how an existing manufacturer can grow at a faster rate by co-investing in tandems. Our analyses highlight potential routes to market for perovskite photovoltaics and the possibility to sustainably grow a photovoltaics manufacturing company even in markets with higher labor rates. We show how technoeconomic modeling of cleantech products versus scale can be an important tool in assisting a more rapid uptake of new energy technologies that often struggle to leave the lab. Our analyses highlight potential routes to market for perovskite photovoltaics and the possibility to sustainably grow a photovoltaics manufacturing company even in markets with higher labor rates. More generally, although technoeconomic modeling has proven to be a useful tool for assessing cleantech industries as they are and the long-term potential of new technologies once they reach scale—we encourage other cost modelers to quantify the impact of economies of scale during manufacturing growth to help in the search for viable and sustainable market on-ramps for their technologies. The significant capex of photovoltaics manufacturing has made it difficult for new cell and module technologies to enter the solar power market. We show how technoeconomic modeling of cleantech products versus scale can be an important tool in assisting the commercialization of new energy technologies that often struggle to leave the lab with our analyses focusing on potential routes to market for perovskite photovoltaics.
CRIS-Team Scopus Importer:2022-06-05
Keywords: cleantech; flexible perovskites; perovskites; photovoltaics manufacturing; sustainable finance; tandem solar cells; technoeconomic modeling